Decrease in macrofauna density increases the sediment phosphorus release and maintains the high phosphorus level of water column in Lake Taihu: A case study on Grandidierella taihuensis. (15th October 2022) - Li, Cai; Ding, Shiming; Cai, Yongjiu; Chen, Musong; Zhong, Zhilin; Fan, Xianfang; Wang, Yan
Highlights: Macrofauna density has dropped by 93% in Lake Taihu from 2007 to 2020. Ventilation causes highly dynamic redox oscillation in the burrows of G. taihuensis . G. taihuensis increases O2 penetration depth by more than 20 mm via bio-irrigation. G. taihuensis bioturbation significantly increases the P retention in sediments. Sharp decline in macrofauna density partly leads to high water column P level. Abstract: Internal phosphorus (P) loading can increase the P level in the water column and further sustains cyanobacterial blooms. This study focused on the role of benthic fauna bioturbation in affecting the sediment P release and the P level of water column in a eutrophic lake, Lake Taihu. The macrofauna density decreased from 4766.56 ± 10541.80 ind/m 2 in 2007 to 345 ± 447.63 ind/m 2 in 2020 due to the frequent bottom-water hypoxia in Lake Taihu. The reduced macrofauna density majorly resulted from Grandidierella taihuensis, Limnodrilus hoffmeisteri, and Tanypus chinensis larvae, and their total density decreased by approximately 97% in 2020 compared to 2007 . G. taihuensis, one of the major benthic faunas, was further used as a representative to investigate the effects of bioturbation on sediment P release using high-resolution sampling and imaging techniques. The results show that G. taihuensis can increase the O2 penetration depth by more than 20 mm through bio-irrigation, and causes the redox conditions in burrows and surrounding sediments to change dramatically within a few minutes due to the intermittent ventilation. Subsequent oxidation of the soluble Fe(II) led to the formation of Fe-oxide bound P in the surface sediments, thereby increasing the P retention in the sediments. When the G. taihuensis density was 1563 ind/m 2 at the sampling site, approximately 0.12 g m −2 yr −1 P can be retained in sediments. As previous studies have shown that L. hoffmeisteri and T. chinensis played a similar role in increasing the P retention in sediments through their bioturbation activities, the sharp decline in benthic fauna density and burrowing activities in Lake Taihu should be an important reason for maintaining the high P level in the water column by decreasing the P retention in sediments. Graphical abstract: Image, graphical abstract